Imminent increased risks is imperative for greater cooperation and global coordination - Barrera Herrera, Jorge (2016)
This article discussed and revised opinions and conclusions that have been determined by researchers working at the IMF and as economists consider of vital importance for analysis and understanding, which states that we are witnessing a growth and global inflation persistently weak and uncertain, despite having taken a number of corrective measures after the 2008 crisis; also a decline of optimism seen, setting the pace for a new normal, which the IMF calls the “new mediocrity,” all this is causing an increase in macroeconomic risks so the IMF recommends that it is imperative that the doers public policy act more than ever jointly and cooperating, acting beyond the current stage set where monetary policies have been the major players so as to provide an environment of trust us out of this slowed normality and to promote a sustained global economic growth avoiding future crises.